A Solution‐Processable High‐Modulus Crystalline Artificial Solid Electrolyte Interphase for Practical Lithium Metal Batteries. Issue 30 (28th June 2022) - Yu, Zhiao; Seo, Samuel; Song, Jongchan; Zhang, Zewen; Oyakhire, Solomon T.; Wang, Yang; Xu, Rong; Gong, Huaxin; Zhang, Song; Zheng, Yu; Tsao, Yuchi; Mondonico, Luca; et al.
Abstract: The solid electrolyte interphase (SEI) has been identified as a key challenge for Li metal anodes. The brittle and inhomogeneous native SEI generated by parasitic reactions between Li and liquid electrolytes can devastate battery performance; therefore, artificial SEIs (ASEIs) have been proposed as an effective strategy to replace native SEIs. Herein, as a collaboration between academia and industrial R&D teams, a multifunctional (crystalline, high modulus, and robust, Li + ion conductive, electrolyte‐blocking, and solution processable) ASEI material, LiAl‐FBD (where "FBD" refers to 2, 2, 3, 3‐tetrafluoro‐1, 4‐butanediol), for improving Li metal battery performance is designed and synthesized. The LiAl‐FBD crystal structure consists of Al 3+ ions bridged by FBD 2– ligands to form anion clusters while Li + ions are loosely bound at the periphery, enabling an Li + ion conductivity of 9.4 × 10 –6 S cm –1 . The fluorinated, short ligands endow LiAl‐FBD with electrolyte phobicity and high modulus. The ASEI is found to prevent side reactions and extend the cycle life of Li metal electrodes. Specifically, pairing LiAl‐FBD coated 50 µm thick Li with industrial 3.5 mAh cm –2 NMC811 cathode and 2.8 µL mAh –1 lean electrolyte, the Li metal full cells show superior cycle life compared to bare ones, achieving 250 cycles at 1 mA cm –2 . Abstract : A multifunctional (solution‐processable, crystalline, mechanically robust, electrolyte‐blocking, and highly ionic conductive) material, LiAl‐FBD (where "FBD" refers to 2, 2, 3, 3‐tetrafluoro‐1, 4‐butanediol), as the artificial solid‐electrolyte interphase to protect lithium metal anodes is rationally designed and synthesized. The lithium metal batteries using LiAl‐FBD coated thin lithium foil, industrial‐scale high‐voltage high‐loading cathodes, and lean electrolyte condition show superior cycling performance to bare ones.